2020
DOI: 10.1055/s-0040-1715441
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Adaptations in Pseudonaja Textilis Venom Factor X Induce Zymogen Activity and Resistance to the Intrinsic Tenase Complex

Abstract: The venom of the Australian snake Pseudonaja textilis comprises powerful prothrombin activators consisting of factor X (v-ptFX)- and factor V-like proteins. While all vertebrate liver-expressed factor X (FX) homologs, including that of P. textilis, comprise an activation peptide of approximately 45 to 65 residues, the activation peptide of v-ptFX is significantly shortened to 27 residues. In this study, we demonstrate that exchanging the human FX activation peptide for the snake venom ortholog impedes proteoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 60 publications
(97 reference statements)
0
8
0
Order By: Relevance
“…Activated FX (FXa) can further form prothrombinase with FVIIa and PCPS. 45 The results can also explain the plasma clotting time prolongation of preconditioning group (thrombin and P-2-CG) because of the decreased thrombin generation amount and prolonged thrombin generation time.…”
Section: ■ Materials and Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…Activated FX (FXa) can further form prothrombinase with FVIIa and PCPS. 45 The results can also explain the plasma clotting time prolongation of preconditioning group (thrombin and P-2-CG) because of the decreased thrombin generation amount and prolonged thrombin generation time.…”
Section: ■ Materials and Methodsmentioning
confidence: 86%
“…The FXa generation amount was also significantly lower in the adherent HUVECs group (0.21 nM FXa), compared with that of the thrombin group (0.27 nM) ( p < 0.001, Figure C). Activated FX (FXa) can further form prothrombinase with FVIIa and PCPS . The results can also explain the plasma clotting time prolongation of preconditioning group (thrombin and P-2-CG) because of the decreased thrombin generation amount and prolonged thrombin generation time.…”
Section: Resultsmentioning
confidence: 99%
“…The intrinsic tenase activation of FX is driven by exosite binding [7], and as previous studies have suggested that the FX‐AP contributes to activator specificity and prevents the promiscuous activation of FX [8,11,19], the FX‐AP may be an important exosite. This was demonstrated in a competitive inhibition study, where a chimeric FX construct containing human FX and the AP of venom‐derived Pseudonaja textilis was a significantly weaker competitor of the intrinsic tenase‐mediated activation of human FX, compared with a nonactivable FX construct containing a Gln substitution of the Arg residue at the P1 site [12]. This suggested that the exosite interactions that drive the intrinsic tenase‐mediated activation of human FX are located both in the FX‐AP and at extended sites on the FX surface outside the FX‐AP.…”
Section: Resultsmentioning
confidence: 99%
“…An emerging proposition for the distinctive substrate specificity of intrinsic tenase is that exosite interactions, rather than recognition of sequences flanking the scissile bond, is a major determinant of biomolecular substrate specificity [7]. The FX-AP is considered to be important for the specificity of the intrinsic tenase complex towards FX [8][9][10][11][12], but details of the molecular role of the FX-AP remain a major question in coagulation biochemistry.…”
mentioning
confidence: 99%
“…Activated FX catalyzes the conversion of prothrombin into thrombin (FIIa) by cleavage at the R271−T272 and R320−I321 residues [87,88] . FXa forms the prothrombinase complex with protein cofactor FVa and Ca 2+ assembled on the PL membrane [89] . Other naturally occurring substrates of FXa include FV, FVII, FVIII, protein S, and FX upon autoactivation (residues are summarized in Figure 5).…”
Section: Coagulation and Fibrinolysis – Proteasesmentioning
confidence: 99%